The Effect of the 5E Learning Model Supported with Material Ensuring Conceptual Change on Science Achievement: The Example of â€œHeat and Temperatureâ€ - IÅŸcan, YÄ±lmaz Vahit Vahit; Seyhan, Hatice GÃ¼ngÃ¶r (Mimbar Sekolah Dasar, 2021)
This study seeks to examine the effect of the 5E learning model, as one of the constructivist learning approach models, supported by conceptual change texts and enriched with relevant guidance materials on eliminating the fifth-grade students' (n=42) misconceptions about "Heat and Temperature". A quantitative research approach was employed by conducting the pre-test and post-test quasi-experimental design of the non-equivalent groups, namely the experimental and control groups. Before the implications, the Heat and Temperature Achievement Test (HTAT) was used to determine the academic achievement levels of the students in the experimental and control groups in the topic of heat and temperature. The pre-test results between both group students did not find a significant difference. There was a significant difference in favor of the experimental group between the HTAT post-test results. From the results obtained within the scope of the study, it was concluded that this learning model was effective in eliminating the fifth-grade students' misconceptions about the topic of heat and temperature.